Answer:
x = -8
y = 9
Step-by-step explanation:
to solve this expression using simultaneous equation, we would say let
y =9............................................. equation 1
6x + 5y =-3............................................equation 2
substitute equation 1 into equation 2
-3 = 6x + 5y............................................equation 2
6x + 5(9) = -3
6x + 45 = -3
collect the like terms
6x = -3-45
6x = -48
divide both sides by the coefficient of x which is 6
6x/6 = -48/6
x = -8
therefore y = 9
x = -8
Let,
Harry's age - x then Nick is 7x.
After 6 years, Harry is x+6 and Nick is 7x+6
So, 7x+6= 5(x+6)=> 2x = 30-6X = 12
In 6 years, Harry will be 12+6 = 18 years (Ans)
The smaller side is 4 units going from point (2,2) to point (6,6) while the biger side is 8 units long going from point (6,6) to point (14,14). So 4 is 1/2 of 8 therefore there is a 1:2 ratio because of 4:8
Answer:ASA stands for (angle-side-angle)
Step-by-step explanation: According to the ASA rule, two triangles are said to be congruent if any two angles and the side included between the angles of one triangle are equal to the corresponding two angles and side included between the angles of the second triangle.
Answer:
Radius
Step-by-step explanation: